2019
DOI: 10.3390/w11061237
|View full text |Cite
|
Sign up to set email alerts
|

Marine Ranching Construction and Management in East China Sea: Programs for Sustainable Fishery and Aquaculture

Abstract: Marine ranching, which is considered a sustainable fishery mode that has advantages for the ecosystem approach to fishery, the ecosystem approach to aquaculture, and capture-based aquaculture, is rapidly growing in China. The development of marine ranching requires integrating different theoretical frameworks, methodological approaches for conceptual exploring, and models and management of ecosystem frameworks. We reviewed the definition of marine ranching, the history of marine ranching construction in China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 101 publications
(113 reference statements)
0
25
0
3
Order By: Relevance
“…New approaches to aquaculture have been recently proposed aiming at reducing habitat degradation, among other benefits (Barrington et al, 2010;Granada et al, 2016;Gunning et al, 2016;Nardelli et al, 2019;Zhou et al, 2019). However, such novel and frequently costly approaches may be considered unnecessary, if site conditions allow for the operation of aquaculture production without noticeable environmental impacts.…”
Section: Discussionmentioning
confidence: 99%
“…New approaches to aquaculture have been recently proposed aiming at reducing habitat degradation, among other benefits (Barrington et al, 2010;Granada et al, 2016;Gunning et al, 2016;Nardelli et al, 2019;Zhou et al, 2019). However, such novel and frequently costly approaches may be considered unnecessary, if site conditions allow for the operation of aquaculture production without noticeable environmental impacts.…”
Section: Discussionmentioning
confidence: 99%
“…A marine ranch is concerned with the sustainable development of marine ecology, marine economy, and fishery production. Several countries, such as China [2], Japan [3], Australia [4], and Norway [5], consider marine ranching as the most promising method to increase fishery resources and stock, and promote sustainable development of fishery resources. In recent years, many researchers have noticed the important role of marine ranching.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [54][55][56] have shown that turbulence may also affect the feeding of marine organisms such as plankton and other fish. Furthermore, turbulent motions in the surrounding flows can be important also for the encounters of aquatic microorganisms and their prey by bringing predators and prey close from time to time and thereby enhancing the probability of capture even without relying on self-induced motions [57][58][59][60][61]. Nevertheless, sometimes, turbulence can also provide organisms with hydrodynamic signals that may be wrongly interpreted as generated by an approaching predator, which may affect their behavior and the energetic cost of swimming [62].…”
Section: Introductionmentioning
confidence: 99%